Entrepreneurial personality traits and SMEs profitability in transition economy - Jovanovic, Ivan; Arsic, Milica; Nikolic, Djordje (Serbian Journal of Management, 2018)
Creativity and innovation have been identified in the literature as the main drivers of small and medium size enterprises’ development. The aim of this study was to determine whether these factors also affect the profitability of the SME sector in Serbia. The conceptual model was set and six hypotheses were proposed. The survey was conducted in South and South-Eastern Serbia, on a sample of 717 small and medium enterprises. CFA and Path Analysis were used to test conceptual model. The results showed high reliability of the data and confirmed hypotheses.